Bulky yet flexible substituents in insertion polymerization with α-diimine nickel and palladium systems 1. Issue 35 (15th August 2019) - Guo, Lihua; Sun, Wenting; Li, Shuaikang; Xu, Guoyong; Dai, Shengyu
Abstract : The bulky yet flexible substituent on the N -aryl moieties of α-diimine ligands may adopt different conformations and provide dynamic steric hindrance in the process of ethylene (co)polymerization. Abstract : Previous studies have shown that the introduction of substituents with rigid steric hindrance into α-diimine ligands results in polymers with improved properties via nickel and palladium catalyzed olefin insertion (co)polymerization. In this contribution, a series of α-diimine nickel and palladium complexes containing bulky yet flexible substituents have been synthesized and characterized. The thermostable nickel complexes in this system show high activity and can generate highly branched polyethylene with high molecular weight. Most interestingly, the polymer products display excellent elastic properties (SR value of up to 88%) characteristic of thermoplastic elastomers. In Pd-catalyzed ethylene (co)polymerization, compared with the classical palladium complexPd0, the presence of flexible substituents inPd1–Pd3 results in lower activity. However, as the tether length of the flexible substituent increases fromPd1 toPd3, a clear trend is observed wherein the catalytic activity and polymer molecular weight increase while the polar monomer incorporation and branching density decrease.